High performance pose invariant face recognition - Demirel, Hasan; Anbarjafari, Gholamreza (Insticc-Inst Syst Technologies Information Control & Communication, 2008)
A novel pose invariant face recognition system based on grey level histogram matching is proposed. The proposed system in this paper uses grey level histograms as feature vectors for recognition of the different poses of faces. The process is performed by taking the cross correlation between the histogram of a test face and the histograms of the training faces in the database. The proposed system gives 98.80% recognition rate on the HP database of 15 face subjects. This rate is down to 92% in the case of conventional eigenfaces method.
3rd International Conference on Computer Vision Theory and Applications -- JAN 22-25, 2008 -- Funchal, PORTUGAL
Keywords: face recognition; pose invariant; histogram matching